Immunological insights into COVID-19 in Southern Nigeria - Ugwu, Chinedu A.; Alao, Oluwasina; John, Oluwagboadurami G.; Akinnawo, Blossom; Ajayi, Israel; Odebode, Ooreofe; Bejide, Ifeoluwa; Campbell, Allan; Campbell, Julian; Adole, Jolly A.; B. Olawoye, Idowu; Akano, Kazeem; et al. (Frontiers in Immunology, 2024)
One of the unexpected outcomes of the COVID-19 pandemic was the relatively low levels of morbidity and mortality in Africa compared to the rest of the world. Nigeria, Africa's most populous nation, accounted for less than 0.01% of the global COVID-19 fatalities. The factors responsible for Nigeria's relatively low loss of life due to COVID-19 are unknown. Also, the correlates of protective immunity to SARS-CoV-2 and the impact of the preexisting immunity on the outcome of the COVID-19 pandemic in Africa are yet to be elucidated. Here, we evaluated the natural and vaccine-induced immune responses from vaccinated, non-vaccinated and convalescent individuals in Southern Nigeria throughout the three waves of the pandemic in Nigeria. We also examined the pre-existing immune responses to SARS-CoV-2 from samples collected prior to the COVID-19 pandemic. Our study demonstrated a similar magnitude of both binding and neutralizing antibody responses from symptomatic and asymptomatic survivors as well as vaccinated participants in Nigeria.Interestingly, we revealed the presence of preexisting binding antibodies but no neutralizing antibodies from samples collected prior to the pandemic. Table 1 The seroprevalence of SARS-CoV-2 S-RBD and N binding (IgG) and neutralizing antibody response among survivors and their contacts in Southern Nigeria. Table 2 Vaccine and convalescent sera distribution